A Tetranuclear Silver-Thiourea Cluster - Fernandes, José A. [UNESP]; Segura, Daniel F.; Netto, Adelino V. G.; Frem, Regina C. G.; Mauro, Antonio E. [UNESP]; Paz, Filipe A. Almeida [UNESP] (Springer Nature, 2015)
During the synthesis of the bioactive complex [Ag(phen)(μ-tu)]2(NO3)2 (1), some crystals of a new compound were isolated. This crystalline compound, [Ag4(μ-tu)5(tu)6](NO3)4·7Phen (2) (tu = thiourea, Phen = 1,10-phenanthroline), is a novelty for at least two reasons: (i) it is the first tetranuclear silver and thiourea cluster; (ii) it is the first crystal structure with seven neutral, and uncoordinated, phen molecules. Phen molecules pack forming an infinite column, and the tu ligands form an intricate network of hydrogen bonds with the Phen and nitrate entities.
Keywords: Silver and thiourea cluster; Supramolecular interactions